Mango Production in Flood Prone Lands of Shibganj Upazila: The Mango Growers’ Perception - Rakib, Md. Abdur; Rahman, Md. Zulfikar; Sarker, Md. Asaduzzaman; Rana, Md. Masud (Journal of the Bangladesh Agricultural University, 2024)
The main purpose of the study was to find out the extent of use of flood prone lands into mango production by planting different mango varieties, to find out the cause and effect of transformation of flood prone lands into mango production, to measure perception of the growers about using flood prone lands to mango production and explore the relationships between the selected demographic characteristics of the farmers and their perception of using flood prone lands to mango production. The study was conducted in four villages of Shibganj upazila under Nawabganj district. The sample size 80, randomly selected from a population of 400 mango growers. Interview schedule was used to collect data. Data were collected personally during 25 July to 15 September, 2015. Pearsons’ product moment correlation co-efficient (r) was computed to explore the relationships between the selected characteristics of the mango growers and their perception on using flood prone lands to mango production. The main three causes of transformation of flood prone lands to mango production were: Mango provides more earning than field crops, the neighbours and other land owners who planted mango trees serve as facilitators for others to follow the same and mango plants once planted give good return for several years; but in case of other crops, one has to grow crops every year. The most important effects of mango cultivation were found: Mango cultivation maintains environmental balance, it helps in earning more money and provide bio-fertilizer by the fallen leaf. The majority (78.75%) of the mango growers possessed high positive perception about mango growing in the flood prone area while 20% had moderate perception about transformation of flood prone lands to mango production. Among the 11 selected socio-economic characteristics of mango growers, eight (08) characteristics namely education, annual income, farm size, cosmopoliteness, media exposure, organizational participation, innovativeness and knowledge on mango production had positive significant relationship with their percerption of using flood prone lands to mango production. The mango growers mentioned a number of problems as well as probable solutions in transformation of flood prone lands to mango production. By taking proper and timely initiatives the transformation process should be enhanced to ensure sustainable quality mango production and socio-economic development of mango growers. J Bangladesh Agril Univ 19(1): 109–118, 2021 https://doi.org/10.5455/JBAU.10735